2021
DOI: 10.1186/s13018-021-02534-y
|View full text |Cite
|
Sign up to set email alerts
|

Repair of symptomatic bilateral L5 spondylolysis with autogenous iliac crest graft and temporary intersegmental pedicle screw fixation in youth

Abstract: Background When symptomatic spondylolysis fail to respond to nonoperative treatment, surgical management may be required. A number of techniques have been described for repair by intrasegmental fixation with good results; however, there are still some problems. We reported a repair technique with temporary intersegmental pedicle screw fixation and autogenous iliac crest graft. The aim of present study is to assess the clinical outcomes of L5 symptomatic spondylolysis with this technique. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Third, because some patients have disc degeneration and spondylolisthesis preoperatively, postoperative pain assessment is di cult due to these confounding factors. However, although patients with these factors have been excluded in previous reports [12,18], they had good outcomes in the present study. Multiple regression analysis including these factors with a larger number of patients is needed in the future.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Third, because some patients have disc degeneration and spondylolisthesis preoperatively, postoperative pain assessment is di cult due to these confounding factors. However, although patients with these factors have been excluded in previous reports [12,18], they had good outcomes in the present study. Multiple regression analysis including these factors with a larger number of patients is needed in the future.…”
Section: Discussionmentioning
confidence: 76%
“…We categorized the pars defect based on the axial CT [12] as follows: type I (line type), in which the gap is almost hairline; type II (intermediate type) shows a clear bone gap with no signs of bone atrophy or sclerosis at the edge of the bony defect; type III (sclerosis type) shows an enlarged bony gap with manifestations of bone atrophy and sclerosis. In the present study, types I and II were included in group A; and type III was included in group B (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are two common methods of internal fixation in clinical practice. One is Buck's technique, proposed by Buck in 1970, to directly fix the isthmus repair, (JE, 1970;Snyder et al, 2014) , and the other is the indirect fixation of the isthmus with the intersegmental pedicle screw internal fixation system used by various scholars (Huang et al, 2019;Zhang et al, 2021). Extensive studies have confirmed the effectiveness and safety of both methods.…”
Section: Introductionmentioning
confidence: 99%
“…Another pedicle screw system ameliorated the low postoperative fusion rate. The strong grip of the pedicle screw itself and the squeezing effect of the screw system on the isthmic bone graft ensure isthmic fusion (Huang et al, 2019;Zhang et al, 2021). However, the above two fixation methods also have certain defects.…”
Section: Introductionmentioning
confidence: 99%